Sejauh Manakah Kurikulum Sekolah Rendah Darjah I Hingga III Menjadi Asas yang Kukuh Sebagai Persediaan Pelajaran - Othman, Ghazali (Penerbit Universiti Sains Malaysia, 1980)
This paper attempts to assessthe extent to which the present primary school curriculum provides a strong foundation in the educational preparation of children in Standard I to Standard III. The review of literature indicates that very little effort has been undertaken to make a comprehensive curriculum review. This is because data on what actually transpires in the classroom is not readily available. Hence. generally, pupils' performances in public examinations have been regarded as indicators of their successful passagethrough a school curriculum. Curriculum factor is assumed to be constant and affects every child in the same way. Thus, variance of success in examination is explained more by other commonly known factors such as family socio-economic status, social environment, genetic composition, etc. No systematic estimation of curriculum factor explaining the variance of one's performance in public examination has been made. This paper is a preliminary, exploratory survey conducted on a sample of school teachers and principals to gather their opinion on the present primary school curriculum. Although the sample is not representative, the opinions expressed seem to reflect the general concern regarding the weaknessesof the present primary school curriculum. Teachers are basically corncerned that the present curriculum is overcrowded; and children at a young age have to learn too many languages, too many topics in sciences and in arithmetic. This paper suggeststhat in implementing a school curriculum teachers should give consideration to individual differences. Curriculum should be more flexible so that teachers could use different methods for different pupils.